Neurological Symptoms and Their Associations With Inflammatory Biomarkers in the Chronic Phase Following Traumatic Brain Injuries - Li, Gangqin; Liu, Hao; He, Yong; Hu, Zeqing; Gu, Yan; Li, Yan; Ye, Yi; Hu, Junmei (Frontiers in Psychiatry, 2022)
Background: The underlying biological mechanisms for neuropsychiatric symptoms following a traumatic brain injury(TBI) remain poorly understood. This study investi-gated the associations between serum inflammatory biomarkers and neuropsychiatric symptoms in the chronic phase following moderate to severe TBI. Methods: The serum interleukin [IL]-1β, IL-4, IL-5, IL-6, IL-7, IL-8, IL-10, IL-12p70, and the tumor necrosis factor [TNF]-α in 72 TBI patients 6 months to 2 years post injury were measured. Neuropsychiatric symptoms including depression, chronic headache, sleep disorders, irritability, anxiety, and global neuropsychiatric disability were assessed. The associations between the biomarkers and the neuropsychiatric symptoms were as-sessed using correlation and regression analysis. Results: It was found that the most common post-injury symptom was sleep disorders (84.7%), followed by chronic headaches (59.7%), irritability (55.6%), and depression (54.2%). TNF-α was a protective factor for chronic headache (OR = 0.473, 95% CI = 0.235-0.952). IL-6 was positively associated with sleep disorders (r = 0.274, p = 0.021), while IL-5 and IL-12p70 were negatively associated with the degree of global neuro-psychiatric disability (r = -0.325, p = 0.006; r = -0.319, p = 0.007). Conclusion: This study provides preliminary evidence for the association between chronic inflammation with neuropsychiatric symptoms following a TBI, which suggests that anti-inflammatory could be a potential target for post-TBI neuropsychiatric reha-bilitation. Further research with larger sample sizes and more related biomarkers are still needed, however, to elucidate the inflammatory mechanisms for this association.